Podjetniška demografija in potencial starejših podjetnikov: Slovenski podjetniški observatorij 2025 - Močnik, Dijana; Bradač Hojnik, Barbara (University of Maribor Press, 2026)
Business Demographics and the Potential of Senior Entrepreneurs: Slovenian Entrepreneurship Observatory 2025. The Slovenian Entrepreneurship Observatory 2025 provides a comprehensive analysis of entrepreneurial demographics and entrepreneurship among older people in Slovenia. In the first part of the study, we examined the key demographic characteristics of Slovenian companies, including their number, size, revenue, labour costs, and added value, broken down by activity, region, and size class. The second part of the study focused on an indepth examination of entrepreneurship in later life, specifically targeting senior entrepreneurs (particularly those aged 55 and above) and their role in entrepreneurial activity, business stability, and job creation. We analysed the characteristics and dynamics of older entrepreneurs, their motives, challenges, and specific needs, particularly in relation to maintaining career activity, adapting to change, and planning business transfers. Based on our findings, we have developed strategic guidelines and proposals for measures for the supportive environment and policymakers in Slovenia.